Morphologic Patterns of Lip Prints in a Sample of Croatian Population - Marija Šimović; Ivan Pavušek; Senad Muhasilović; Marin Vodanović (Acta Stomatologica Croatica, 2016)
Purpose: Cheiloscopy deals with the study of elevations and depressions which form a characteristic pattern on the external surface of the lips. Lip grooves are considered to be unique and analogous to the fingerprint. The aim of the research was to determine the type of grooves on healthy lips of men and women using lip prints in a sample of Croatian population, to determine whether there is a statistically significant difference between men and women in the types of grooves and to determine whether there are any differences between male and female lip prints. Material and methods: A randomly selected sample of Croatian population consisted of 40 male and 50 female subjects. The samples of lip grooves were classified according to Tsuchihashi classification. Results: The research has shown that most women in Croatia belong to Type 2 (40.0%), followed by Type 1 (34.0%), Type 3 (12.0%), Type 4 (8.0%), and Type 5 (6.0%) which is of less importance. Most Croatian men belong to Type 3 (35.0%) and Type 2 (25.0%). A small number of men belong to Type 4 (15.0%), Type 5 (12.5%) and Type1 (12.5%). Conclusion: There was a statistically significant difference between men and women regarding the types of lip grooves.